How destination brand experience influences tourist citizenship behavior: Testing mediation of brand relationship quality and moderation effects on commitment - Tang, Jinwen; Wang, Jingna; Zhang, Min; Huang, Weizhao (Frontiers in Psychology, 2023)
This study examines the potential predictors of tourist citizenship behaviour based on the Stimulus–Organism–Response framework. This model was used to test the hypotheses using a sample of 325 individuals with tourism experience in Guangzhou city. The results reveal that tourism destination brand experience and brand relationship quality significantly affect tourist citizenship behaviour. Furthermore, the results show that brand relationship quality significantly mediates the relationship between tourism destination brand experience and tourist citizenship behaviour and demonstrate that commitment plays a significant moderating role between brand relationship quality and tourist citizenship behaviour. This study clearly shows the relationship between tourism destination brand experience, brand relationship quality, and tourist citizenship behaviour. Thus, this study contributes to existing tourism studies by identifying gaps and proposing a holistic view to understand tourist citizenship behaviour in the tourism industry.